Roles of Foliar Fertilization on Growth, Yield and Quality of Tomato (Solanum lycopersicum L.) Cultivars (Review) - Daniel Munda; Fanuel Laekemariam; Yitbarek Abrham (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Tomato (Solanum lycopersicum L.) is one of the most important vegetable crops, and it is a source of daily diet and cash crop in Ethiopia. However, its production is affected by nutrient application methods of which foliar fertilization is a popular method. The objective of this review paper is to synthesize literatures on the effects of foliar fertilization on growth, yield and quality of tomato cultivars. Both macro and micronutrient concentrations were evaluated. The articles addressing that foliar fertilization effectively increased growth, yield and quality of tomato cultivars.  Foliar fertilization to be effective and maximize crop yield and nutrient uptake, the "right type," "right rate," "right time “and” right place" are essential. The right nutrient selection satisfies crop requirements, and the optimal rate of application avoids stunted development. Applications should be timed for optimal absorption conditions to maximize efficacy and avoid waste by focusing on absorbent plant sections. These elements work together to promote sustainable and effective crop management. Over all, the results showed that with 10,000 ppm of urea fertilization, the Marglobe tomato cultivar achieved a plant height of 155.63 cm, fruit weight of 151 g, and a yield of 63.69 t/ha. Additionally, the findings indicated 9.05 ± 0.32% total soluble solids (TSS) and a chlorophyll content of 51.6 ± 1.31 SPAD values with 100 ppm of ZnO nanoparticles. In conclusion, foliar fertilization of nutrients increased growth, yield and quality of tomato cultivars however, the result vary from cultivar to cultivar. The foliar fertilization depends on appropriate time, weather condition, genotypes of tomato, leaf area index, amount of foliar fertilization, type of nutrient, and stage of crop.